Motivasi Meraih Pendidikan: Peran Keluarga Dan Lingkungan Sebagai Jembatan Utama Bagi Anak Di Desa Cipancar, Kecamatan Leles, Kabupaten Garut - Daryadi, Yudi; Faruqi, Jihad; Fadilah, Yukeu; Nugraha, Nabila Apriliani; Ariandini, Luthfi; Dzaky Ilyas, Muhammad Yassir; Sunani, Indy; Yulianti, Selviana Putri; Hadianti, Revi Silvi; Pratomo, Nida Balqis; Ismail, Putuh (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2024)
This community service aims to analyze the role of family and environment as the main factors in building children's motivation in Cipancar Village, Leles District, Garut Regency to achieve education. Education is an important foundation for individual and community development, especially in rural areas that often face limited access and resources. The family acts as an early motivator in providing moral, emotional and material support to children, thus encouraging them to achieve academically. This study used a qualitative approach with data collection through socialization conducted with parents, children, teachers and community leaders to understand how family and environmental interactions affect children's character. Researchers also conducted observations of children in the Cipancar Village environment to see direct behavior that reflects the values taught. The results showed that the synergy between the roles of family and environment significantly increased children's motivation to achieve better education. However, economic factors are still a major obstacle that needs more attention, especially in providing wider and more equitable access to education. With a better understanding of the importance of the roles of family and environment, it is hoped that there will be an overall improvement in the motivation and quality of education in Cipancar village.